(untitled) (REMUNOM, 2024)
The work addresses the health management of goats and sheep, aiming to promote the health and well-being of these animals, in addition to ensuring the sustainability of breeding. The context involves the growing importance of the production of these species in agriculture, both for human consumption and for various economic activities. The main objective is to highlight the relevance of appropriate health management practices in preventing diseases and promoting the productivity and profitability of goat and sheep farming. The methodology included a bibliographic review of scientific studies and analysis of good management practices adopted by experienced producers. The results obtained demonstrated that the implementation of an effective health management program, involving vaccination, parasite control, facility hygiene and balanced nutrition, contributes significantly to the health and performance of the animals. Furthermore, raising awareness among producers and adopting preventive measures are essential for the success of livestock farming. The conclusion highlights the importance of investing in adequate health management practices as a fundamental strategy to ensure the competitiveness and sustainability of goat and sheep production. These measures not only protect the health of animals, but also promote food security and the well-being of consumers, in addition to contributing to the preservation of the environment and the economic development of rural communities.